Transformed by Crisis
X, 216 p.
Keywords: The presidency of George W. Bush has been a curious one: born in contention, challenged by the most dramatic foreign directed attack on American soil, and transformed by a combination of crisis and conflict that has generated considerable support domestically. And yet, while much attention has been focused on the Bush administration's extrernal policies, how it has pursued its goals and had its effects on the domestic scene has been as important. Examining the push and pull of the Bush presidency by looking especially at domestic dynamics, the authors look at the tendency towards centralizing power and its implications for American politics. From the midterm elections of 2002, where the Republicans scored historic victories, to relations with the press, and from executive branch relations with Congress to increased federal involvement in education, the authors examine and shed light on crucial issues. This book examines how words and deeds in a time of crisis will define the Bush presidency place in American politics and history.